Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Matematika Siswa Kelas V di SD Negeri Sindangbarang 04 (Indo-MathEdu Intellectuals Journal, 2025)
Mathematics learning in primary schools still faces various challenges, one of which is low student learning outcomes due to the use of learning models that tend to be conventional. One alternative that is considered capable of overcoming this problem is the application of the Problem-Based Learning (PBL) model, which emphasises contextual problem solving to increase student active engagement. This study aims to determine the effect of the Problem-Based Learning model on the mathematics learning outcomes of fifth-grade students at SD Negeri Sindangbarang 04. This study uses a quantitative approach with a quasi-experimental design, comparing student learning outcomes before and after the implementation of the PBL model. Data were collected through learning outcome tests and analysed using relevant statistical techniques. The results showed that the implementation of the Problem-Based Learning model had a positive effect on improving students' mathematics learning outcomes, as indicated by an increase in the average score and the percentage of learning completeness. These findings indicate that the PBL model is effective in improving mathematical concept understanding and encouraging more meaningful learning for primary school students.